Upaya Meningkatkan Hasil Belajar Ilmu Pengetahuan Alam Materi Ciri Makhluk Hidup melalui Implementasi Pembelajaran Kooperatif Tipe Team Assisted Individualization (TAI) pada Siswa Kelas VI SDN 2 Rawa Laut, Bandar Lampung - Saleh, Dentiana (LPPM STKIP PGRI Bandar Lampung, 2021)
Based on the results of the pretest conducted on July 30, 2016 it was found that out of 28 students only 10 students or 35.7% scored above the KKM, namely 65. While 10 students or 64.3% had not completed. The low learning outcomes of students in Class VI is caused by several factors. One of them is the monotony of the learning process. Teachers have not implemented innovative and fun learning. Learning delivered by the lecture method, only makes learning run in one direction. In one-way learning, students are considered as learning objects. Problem solving used in this study is to apply the Cooperative learning model type Team Assisted Individualization (TAI). This research is a classroom action research which consists of 3 cycles. The research subjects were teachers (researchers) and sixth grade students at SDN 2 Rawa Laut Bandar Lampung with a total of 28 students. As an observer, the researcher's colleagues were chosen. The variable of this research is Learning Outcomes. Data were collected using test and non-test techniques. Data analysis used quantitative and qualitative descriptive analysis. The results showed that: (1) The students' average scores increased. At the pre-cycle stage of 60.71; in the first cycle got a score of 65.00; increased in the second cycle to 71.79; and increased again in the third cycle to 76.43; (2) Mastery of student learning has increased. At the pre-cycle stage, student learning completeness is 35.7%; increased in the first cycle to 53.6%; increased in the second cycle to 67.9%; and again increased in cycle III to 85.7%. The conclusion of this study is that through the implementation of the Team Assisted Indovidualization (TAI) cooperative learning model, the quality of science learning material on the characteristics of living things in class VI students of SDN 2 Rawa Laut Bandar Lampung has increased. Suggestions from researchers are teachers are advised to learn the steps of learning and prepare all devices before learning begins so that learning objectives can be achieved optimally; Teachers are active in innovating learning so that learning is not boring.